Combination of the Topical Photodynamic Therapy of Chloroaluminum Phthalocyanine Liposomes with Fexinidazole Oral Self-Emulsifying System as a New Strategy for Cutaneous Leishmaniasis Treatment - Raphaela Ariany Silva; Danielle Soter Damasio; Larissa Dutra Coelho; Eliane de Morais-Teixeira; Celso M. Queiroz-Junior; Paulo Eduardo Souza; Ricardo Bentes Azevedo; Antônio Tedesco; Lucas Antônio Ferreira; Mônica Cristina Oliveira; Marta Gontijo Aguiar (MDPI AG, 2024)
Cutaneous leishmaniasis (CL) is a neglected tropical disease. The treatment is restricted to drugs, such as meglumine antimoniate and amphotericin B, that exhibit toxic effects, high cost, long-term treatment, and limited efficacy. The development of new alternative therapies, including the identification of effective drugs for the topical and oral treatment of CL, is of great interest. In this sense, a combination of topical photodynamic therapy (PDT) with chloroaluminum phthalocyanine liposomes (Lip-ClAlPc) and the oral administration of a self-emulsifying drug delivery system containing fexinidazole (SEDDS-FEX) emerges as a new strategy. The aim of the present study was to prepare, characterize, and evaluate the efficacy of combined therapy with Lip-ClAlPc and SEDDS-FEX in the experimental treatment of Leishmania (Leishmania) major. Lip-ClAlPc and SEDDS-FEX were prepared, and the antileishmanial efficacy study was conducted with the following groups: 1. Lip-ClAlPc (0.05 mL); 2. SEDDS-FEX (50 mg/kg/day); 3. Lip-ClAlPc (0.05 mL)+SEDDS-FEX (50 mg/kg/day) combination; 4. FEX suspension (50 mg/kg/day); and 5. control (untreated). BALB/c mice received 10 sessions of topical Lip-ClAlPc on alternate days and 20 consecutive days of SEDDS-FEX or FEX oral suspension. Therapeutical efficacy was evaluated via the parasite burden (limiting-dilution assay), lesion size (mm), healing of the lesion, and histological analyses. Lip-ClAlPc and SEDDS-FEX presented physicochemical characteristics that are compatible with the administration routes used in the treatments. Lip-ClAlPc+SEDDS-FEX led to a significant reduction in the parasitic burden in the lesion and spleen when compared to the control group (p < 0.05) and the complete healing of the lesion in 43% of animals. The Lip-ClAlPc+SEDDS-FEX combination may be promising for the treatment of CL caused by L. major.